2014
DOI: 10.1186/1756-0500-7-536
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and lower TGF-β/IL-17 ratio in a North Indian cohort of pemphigus vulgaris

Abstract: BackgroundPemphigus vulgaris (PV) is an autoimmune bullous disease caused by acantholysis of keratinocytes due to pathogenic desmoglein-3 autoantibodies. Role of vitamin D has been recently implicated in various autoimmune conditions due to its immunomodulatory effects on innate and adaptive immune responses. One of the key mechanisms of the immune regulation by vitamin D is through its anti-inflammatory effects by suppression of Th17 functions. Thus, vitamin D may be involved in pathogenesis of PV. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
4
27
0
2
Order By: Relevance
“…Several epidemiological studies demonstrated that the vitamin D deficiency leads to an increased prevalence of autoimmune diseases, such as the multiple sclerosis, diabetes type 1, rheumatoid arthritis or systemic lupus erythematosus (Yang et al, 2013, Dankers et al, 2017. More recently, the role of vitamin D has been also investigated in AIBD and the emerging evidence suggests an increased frequency of vitamin D deficiency/insufficiency in patients with pemphigus and pemphigoid, such as the PV and BP or EBA, respectively (Marzano et al, 2012 andMarzano et al, 2015;Tukaj et al, 2013;El-Komy et al, 2014;Joshi et al, 2014;Zarei et al, 2014;Moravvej et al, 2016;Sarre et al, 2016;Tukaj et al, 2018) (Table 1). In addition, in some reports, lower concentrations of 25(OH)D have been associated with AIBD activity, pointing towards a possible causative role of hypovitaminosis D in the disease process (Zarei et al, 2014;Marzano et al, 2015;Moravvej et al, 2016).…”
Section: Vitamin D Status In the Autoimmune Bullous Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies demonstrated that the vitamin D deficiency leads to an increased prevalence of autoimmune diseases, such as the multiple sclerosis, diabetes type 1, rheumatoid arthritis or systemic lupus erythematosus (Yang et al, 2013, Dankers et al, 2017. More recently, the role of vitamin D has been also investigated in AIBD and the emerging evidence suggests an increased frequency of vitamin D deficiency/insufficiency in patients with pemphigus and pemphigoid, such as the PV and BP or EBA, respectively (Marzano et al, 2012 andMarzano et al, 2015;Tukaj et al, 2013;El-Komy et al, 2014;Joshi et al, 2014;Zarei et al, 2014;Moravvej et al, 2016;Sarre et al, 2016;Tukaj et al, 2018) (Table 1). In addition, in some reports, lower concentrations of 25(OH)D have been associated with AIBD activity, pointing towards a possible causative role of hypovitaminosis D in the disease process (Zarei et al, 2014;Marzano et al, 2015;Moravvej et al, 2016).…”
Section: Vitamin D Status In the Autoimmune Bullous Diseasesmentioning
confidence: 99%
“…In addition, in some reports, lower concentrations of 25(OH)D have been associated with AIBD activity, pointing towards a possible causative role of hypovitaminosis D in the disease process (Zarei et al, 2014;Marzano et al, 2015;Moravvej et al, 2016). The role of vitamin D deficiency in AIBD, however, is still a matter of debate because other studies have found no difference in the 25(OH)D levels between patients and healthy subjects, possibly due to concomitantly observed low vitamin D levels in the corresponding controls and/ or limited number of patients and controls involved in the study (Tukaj et al, 2013;Joshi et al, 2014;Moravvej et al, 2016;Sarre et al, 2016).…”
Section: Vitamin D Status In the Autoimmune Bullous Diseasesmentioning
confidence: 99%
“…VDR expression on monocytes and T cells allows vitamin D to exert immunomodulatory effects on a transcriptional level and downregulate proinflammatory cytokines . Hypovitaminosis D can thus result in immune dysregulation and is associated with an increased prevalence of autoimmune diseases . Notably, pemphigoid patients have hypovitaminosis D which correlates with increased disease severity .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…208 Hypovitaminosis D can thus result in immune dysregulation and is associated with an increased prevalence of autoimmune diseases. [209][210][211] Notably, pemphigoid patients have hypovitaminosis D which correlates with increased disease severity. 212 In preclinical trials, mice receiving prophylactic oral calcitriol experienced milder skin lesions and histologically less intense dermal infiltration of neutrophils.…”
Section: Heat Shock Protein 90 Inhibitionmentioning
confidence: 99%
“…Joshi et al . examined the serum IL‐17 and TGF‐β levels of PV patients by enzyme‐linked immunoassay and found that all the PV patients had elevated serum IL‐17 levels, whereas it was not detectable in any healthy controls . The mean serum TGF‐β concentration was also lower in patient sera as compared with healthy control, and the TGF‐β/IL‐17 ratio was drastically reduced in patients.…”
Section: T‐cell Regulation Of Autoantibody Production In Pemphigusmentioning
confidence: 99%